Parenting Self-Efficacy Ibu dalam Mengasuh Anak dengan Disabilitas - Trihastuti, Maria Claudia Wahyu; Panggabean, Hana; Marta, Rustono Farady (INKLUSI, 2023)
Parenting self-efficacy ibu, tantangan dan peran lingkungan, disabilitas    This article focuses on the dynamic process of acceptance and motivation as well as essential factors in a mother’s parentingself-efficacy. Six participants are mothers of children (above 6 years old) with either one of the three types of ability: intellectual, sensory, or mental disability. The data are gathered through semi-structured interviews. The result of this study shows that the experienceof being reared by parents becomes a representative experience that adds to mothers’ knowledge and expertise in mothers’ reared task, in that mother’ rearing duty, shows motivation to increase the competency in fostering children with disability in many ways, among others are reading from mass media, consulting with a therapist, and communicating intensively with the teacher. Affiliate stigma experienced by mothers, evokes mothers to be more selective in choosing a social environment that supports the development of children with disability. Spirituality and social support become factors that play a role in mothers’ parenting-self efficacy. Artikel ini membahas dinamika proses penerimaan dan motivasi sebagai faktor yang berperan dalam parenting self-efficacy ibu. Enam responden yang terlibat dalam penelitian ini merupakan ibu dari anak dengan disabilitas (berusia di atas enam tahun) yang memiliki salah satu jenis dari tiga jenis disabilitas yakni intelektual, sensorik, dan mental. Teknik wawancara semi terstruktur digunakan sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa pengalaman diasuh oleh orang tua menjadi pengalaman perwakilan yang menambah pengetahuan dan kemampuan ibu dalam tugas pengasuhan. Ibu menunjukkan motivasi untuk meningkatkan kompetensi dalam mengasuh anak dengan disabilitas melalui berbagai cara, antara lain membaca informasi dari media massa, berkonsultasi dengan terapis, dan berkomunikasi secara intensif dengan guru. Affiliate stigma yang dialami ibu menggugah ibu untuk lebih selektif dalam menentukan lingkungan sosial yang mendukung perkembangan anak disabilitas. Spiritualitas dan dukungan sosial menjadi faktor yang berperan dalam parenting self-efficacy ibu.